2x+3(2x+3)=50+x

Simple and best practice solution for 2x+3(2x+3)=50+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3(2x+3)=50+x equation:


Simplifying
2x + 3(2x + 3) = 50 + x

Reorder the terms:
2x + 3(3 + 2x) = 50 + x
2x + (3 * 3 + 2x * 3) = 50 + x
2x + (9 + 6x) = 50 + x

Reorder the terms:
9 + 2x + 6x = 50 + x

Combine like terms: 2x + 6x = 8x
9 + 8x = 50 + x

Solving
9 + 8x = 50 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
9 + 8x + -1x = 50 + x + -1x

Combine like terms: 8x + -1x = 7x
9 + 7x = 50 + x + -1x

Combine like terms: x + -1x = 0
9 + 7x = 50 + 0
9 + 7x = 50

Add '-9' to each side of the equation.
9 + -9 + 7x = 50 + -9

Combine like terms: 9 + -9 = 0
0 + 7x = 50 + -9
7x = 50 + -9

Combine like terms: 50 + -9 = 41
7x = 41

Divide each side by '7'.
x = 5.857142857

Simplifying
x = 5.857142857

See similar equations:

| 0=-0.005x^2+0.41x-5.1 | | 5x-4=2-x/2 | | (c-8)(-8)= | | Log(9)+7log(x)=2 | | 6(5x-3)=2(x+8) | | 5x+6+6x=6 | | 21=b/8 | | -5=-2p-(-6) | | 10=3f/2-f | | 10x+16x+6=180 | | x+6-6=0+6 | | 3x(2x+3)-5(2x+3)= | | -4.9x=16.27 | | 7+x+2x=19 | | 10q=210 | | 4(b+6)=2(b+5+2) | | 2s+4=5(-4-25) | | 1-7x-3x=-49 | | a+bi=-12+8i | | -8=(K-6)/8 | | 0.9(2x+8)=20-x+5 | | (125)^2/9*(125)^1/9 | | sin(2x)-sin(x)-2cos(x)+1=0 | | -8=K-6/8 | | (1/y^6)^-6 | | B=5.70-5f/3 | | 3=n-21/16 | | 18x+9=3x^2 | | X-14.7=8.02 | | 3b+5f=5.7 | | 1/4(x-7)=1-3x | | (3a-4)/5=-4 |

Equations solver categories